FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN POLA ASUH IBU DALAM MENGAWASI PENGGUNAAN SMARTPHONE PADA ANAK USIA DINI DI KOTA SEMARANG - Hadijah, Rahmatu (Jurnal Ilmu Keperawatan Komunitas, 2025)
In Central Java Province, the percentage of young children who have used smartphones has reached 38.48%, while 33.96% of them have been able to access the internet. This figure is certainly quite worrying because it exceeds the national average data. Young children who use smartphones without parental supervision can be at risk of becoming addicted and suffering from several health problems, both physical and psychological. This study aims to analyze factors related to mothers' parenting practices in supervising smartphone use in early childhood. This research is a quantitative research with a cross sectional study design. The population of this study is mothers who have children aged 4 - 6 years and are able to use smartphones with an estimated number of 70,947 people. The sample was calculated using the Lemeshow formula and the results obtained were 95 people. The data collection technique was carried out by filling out a questionnaire in the form of a questionnaire which was carried out by the mother of the target (children aged 4 - 6 years). Research data was analyzed using SPSS statistical software with univariate and bivariate analysis. Bivariate analysis was carried out using the chi-square test. The results of the bivariate analysis showed that several variables were related to mothers' parenting practices in supervising smartphone use in early childhood are, employment (p=0.004), children's smartphone ownership (p=0.001), knowledge (p=0.004), and attitudes (p=0.009). Variables that are not related to parenting patterns in monitoring smartphone use in early childhood are the highest level of education (p=0.302), marital status (p=0.405) and age (p=0.193). Based on the research results, it is hoped that respondents or mothers can be consistent in supervising children who use smartphones and preventing them from the risk of dependence